Evaluation of the Think First head and spinal cord injury prevention program. Issue 2 (June 1995) - Wright, M.; Rivara, F. P.; Ferse, D.
Abstract : OBJECTIVE: Evaluation of the impact of the Think First head and spinal cord injury prevention program on knowledge, attitudes, and behavior of 11-15 year old students toward injury risks and preventive strategies. SETTING: Three junior high and three senior high schools in rural and urban areas of Washington state. METHODS: Questionnaire survey before intervention, two weeks and three months after intervention to assess knowledge, attitude, and self reported behavior change. Observations of students as they left school property to determine bicycle helmet and seat belt use. RESULTS: Little impact on attitudes and no consistent change in knowledge or self reported behaviors. Too few students rode bicycles to accurately assess helmet use; no consistent change in seat belt use. CONCLUSION: The Think First program appears to have little impact on changes in knowledge, self reported behavior, or observed behavior. Other strategies to decrease injuries in adolescents may be more successful.